A preclinical study of diffusion‐weighted MRI contrast as an early indicator of thermal ablation. Issue 4 (11th November 2020) - Allen, Steven P.; Prada, Francesco; Xu, Zhiyuan; Gatesman, Jeremy; Feng, Xue; Sporkin, Helen; Gilbo, Yekaterina; DeCleene, Sydney; Pauly, Kim Butts; Meyer, Craig H.
Abstract : Purpose: Intraoperative T2 ‐weighted (T2‐w) imaging unreliably captures image contrast specific to thermal ablation after transcranial MR‐guided focused ultrasound surgery, impeding dynamic imaging feedback. Using a porcine thalamotomy model, we test the unproven hypothesis that intraoperative DWI can improve dynamic feedback by detecting lesioning within 30 minutes of transcranial MR‐guided focused ultrasound surgery. Methods: Twenty‐five thermal lesions were formed in six porcine models using a clinical transcranial MR‐guided focused ultrasound surgery system. A novel diffusion‐weighted pulse sequence monitored the formation of T2‐w and diffusion‐weighted lesion contrast after ablation. Using postoperative T2‐w contrast to indicate lesioning, apparent intraoperative image contrasts and diffusion coefficients at each lesion site were computed as a function of time after ablation, observed peak temperature, and observed thermal dose. Lesion sizes segmented from imaging and thermometry were compared. Image reviewers estimated the time to emergence of lesion contrast. Intraoperative image contrasts were analyzed using receiver operator curves. Results: On average, the apparent diffusion coefficient at lesioned sites decreased within 5 minutes after ablation relative to control sites. In‐plane lesion areas on intraoperative DWI varied from postoperative T2‐w MRI and MR thermometry by 9.6 ± 9.7 mm 2 and ‐ 4.0 ± 7.1 mm 2, respectively. The 0.25, 0.5, and 0.75 quantiles of the earliest times of observed T2‐w and diffusion‐weighted lesion contrast were 10.7, 21.0, and 27.8 minutes and 3.7, 8.6, and 11.8 minutes, respectively. The T2‐w and diffusion‐weighted contrasts and apparent diffusion coefficient values produced areas under the receiver operator curve of 0.66, 0.80, and 0.74, respectively. Conclusion: Intraoperative DWI can detect MR‐guided focused ultrasound surgery lesion formation in the brain within several minutes after treatment.